2021
DOI: 10.1177/22104917211039522
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to evaluate disc degeneration on magnetic resonance imaging in patients with chronic low back pain and asymptomatic individuals

Abstract: Objectives The present study aimed to investigate the association of disc degeneration with low back pain and the effect of ageing on disc degeneration in low back pain versus asymptomatic individuals. Methodology A total of 50 patients with chronic low back pain (Group A) were compared to 25 healthy controls (Group B). Both the groups were subjected to magnetic resonance imaging of the lumbar spine and the disc degeneration was measured by the Pfirrmann grading system. The study group (Group A) was further su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
4
2
0
Order By: Relevance
“…9 One more research demonstrated that main MRI imaging features of disc herniation are usually at L4-L5 and L5-S1 levels in both genders. 13 These imaging features are in line with one more study which also showed the evidence that the spinal canal was smallest in both men and women at the level of L5-S1 and widest at L1-L2. 14 Our study shows the average age 45 years (mean age 44.64 years) in patients with complaints of low back ache.…”
Section: Resultssupporting
confidence: 88%
“…9 One more research demonstrated that main MRI imaging features of disc herniation are usually at L4-L5 and L5-S1 levels in both genders. 13 These imaging features are in line with one more study which also showed the evidence that the spinal canal was smallest in both men and women at the level of L5-S1 and widest at L1-L2. 14 Our study shows the average age 45 years (mean age 44.64 years) in patients with complaints of low back ache.…”
Section: Resultssupporting
confidence: 88%
“…The most common site of degenerative changes of lumbosacral spine was L4-5 followed by L5-S1 level, and the least was L2-3 in accordance with other studies [17,26,[28][29][30][31]. As regards the disc morphology, the commonest type was disc protrusion (48%), 32.5% showed disc bulge, and 6.5% had disc extrusion and sequestration, and this agreed with Ravikanth et al [17]; they found that the commonest type was disc protrusion (69.4%).…”
Section: Discussionsupporting
confidence: 90%
“…26 We concur with the literature that pain does not necessarily associated with degenerative discs. 14,26 However, it is possible that LBP is predisposed to the specific degeneration patterns and intensity linked to abnormal orientation. We are of the opinion that the orientation of the disc in the vertebral column plays a crucial role in transmission biomechanical forces and any alteration in it may predispose to back pain.…”
Section: Discussionsupporting
confidence: 89%
“…[23][24][25] The significant normal variation in the sagittal alignment of the spine between asymptomatic people and back pain sufferers has also been noted in earlier research. 16,23,24,26 According to Singh et al, a disc's abnormal orientation may render it more susceptible to degeneration. 26 We concur with the literature that pain does not necessarily associated with degenerative discs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation